Morphological, Biochemical and DNA Studies for the Development of Markers for the Selection of Theobroma Cacao L. Clones Resistant to Vascular Streak Dieback Disease - Kasran, Rosmin (1999)
Vascular streak dieback (VSO) is a serious disease of Theobroma cacao L. (cocoa) plant and it is attributed to the fungal pathogen Oncobasidium theobromae. Control of the disease is largely dependent on the use of systemic fungicides. Resistance to the pathogen had been found in the cocoa planting materials but as yet there was no marker to select for the resistant clones. In relation to this, this study was conducted to develop suitable markers for selection of cocoa clones resistant to a VSO disease. These include morphological, biochemical, enzyme activity, isozyme pattern, light and electron microscopy, and DNA markers. The cocoa clones chosen represented three levels of resistance to VSD disease. The reported resistant clones were MHP80, SCA6, AMA 15-15, ICS95, PA13, KKM25 and SCA9; moderately resistant clones were PBC140, KKM22 and MHP136, while the susceptible clones were MJS21, ICS84, NA32, NA33, UA13, MHP14, MHP3?, PAY, IMC67 and EET 399. The results showed that the morphological characteristics of leaf (shape, color and size), pod (color, shape and surface) and bean (shape, size and and cotyledon color) could not be used to distinguish between the cocoa clones resistant and susceptible to VSD disease. The results on the biochemical and enzyme parameters indicated that the activity of polyphenol oxidase and concentration of chitinase in cocoa leaf tissues were related to resistance to VSD disease. The level of both enzymes were significantly higher (P≤0.05) in the resistant cocoa clones compared to the susceptible clones. Others biochemical parameters such as the concentration of total soluble phenol and β-1,3-glucanase, activity of peroxidase, proteins and isozyme patterns could not distinguish the resistance of cocoa clones to VSD disease. Studies on light microscopy showed that the growth of Oncobasidium theobromae in the leaves of resistant clones resulted in less hyphae compared to those from the susceptible clones. However, the results from the electron microscope studies showed that the infected tissues of both resistant and susceptible cocoa clones showed similar damage symptoms such as cell shrinkage and plasmolysis. The results on Amplified Fragment Length Polymorphism (AFLP) technique to distinguish between cocoa clones that are resistant and susceptible to a VSD disease using selected primer combinations showed polymorphisms among cocoa clones. However, the similarity index and cluster analysis obtained from the data could not classify the cocoa clones as being resistant or susceptible to VSD disease. Meanwhile, a cloned unique fragment of resistant cocoa clone obtained from an AFLP analysis was able to differentiate between resistant (ICS95, KKM25, MHP80, A MA15-15) and susceptible (NA32, PA7, MHP14, MHP37) cocoa clones. This DNA marker was named VSDr1.